IDENTIFIKASI KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI PENCEMARAN LINGKUNGAN - Solihah, Badriatus; Hadi, Wiwin Puspita; Qomaria, Nur; Tamam, Badrud; Rakhmawan, Aditya (Natural Science Education Research, 2023)
This study aims to identify students' critical thinking skills on environmental pollution material. This research uses a descriptive quantitative research design. The research was carried out at SMP ARRAUDHAH Sebaneh Bangkalan with a population of all VIII grade students on environmental pollution. Based on the results of the study it can be concluded that 1. Students' critical thinking skills are said to be in the high category (at least when compared to the other 2 categories, namely only 7 students out of 60 students or 11%. Most critical thinking abilities are in the medium category (34 equal or less than X less than 67), namely 40 students out of 60 students or 70%. Students who have a low critical thinking ability category (67 equal or less than X less than 100) are 13 students out of 60 students or 19%. critical students of 42 which are in the low category. While the results of the assessment of each indicator in this study, namely indicator 1 providing a simple explanation obtained as much as 40%, indicator 2 building basic skills obtained as much as 65%, indicator 3 concluding obtained as much as 60%, indicator 4 making further explanation as much as 45%, and indicator 5 formulates a strategy of 39%.